أثر برنامج تدريبي باستخدام طريقة التبادلي على السرعة الهوائية القصوى والارتقاء لدى لاعبي كرة القدم تحت 17 سنة - سايحي, فؤاد; عامر عامر, حسين; مسالتي, لخضر (Journal of Sport Science Technology and Physical Activities, 2020)
The study aims at identifying the contribution of the training program which is based on short intermittent of Speed Maximum Aerobic and Vertical Relaxation in The Under 17 football players, there 28 players were selected randomly from the research group a and were visited into the control and experimental groups. Through analyzing the results, the researcher was concluded that the training program based on intermittent short training contributed positively to developing speed maximum aerobic and vertical relaxation in the under 17 footballers.